PENINGKATAN KAPASITAS PENGELOLAAN KEUANGAN, PERPAJAKAN, DAN MANAJEMEN RISIKO PADA UMKM SPBU PERDANA SAWERIGADING - Sultan, Sultan; Kasran, Muhammad; Thamrin, Andi Nurlinda; Riyanti, Riyanti; Syamsuddin, Sofyan; Sahrir, Sahrir; Patra, I Ketut; Patangkin, Imelda; Irma, Irma (Universitas Mataram, 2024)
Every company, including MSMEs, must have accurate financial statements that comply with financial accounting standards, as this is important to maintain the financial health of the business. In addition, tax compliance and the implementation of good risk management are also challenges that must be faced by MSMEs to ensure business continuity in the midst of various operational risks. This service program aims to increase the capacity of financial management, tax understanding, and risk management in partners, The activities carried out include the creation and implementation of a simple financial system, tax training, and the implementation of risk management strategies that are tailored to the characteristics of the partner's business. The process of implementing the activity was carried out in several stages of activities, including Focus Group Discussion (FGD), the creation and implementation of financial system applications, taxation training, and risk management training, followed by socialization through training. Monitoring and evaluation are carried out to ensure that partners are able to use the system properly, as well as benefit from the technical training provided. The results of this service activity show that partners have experienced significant improvements in financial management, including more orderly recording and reporting of finances and in accordance with accounting standards. In addition, partners' understanding of tax obligations has also improved, shown by better compliance in complying with tax regulations. Not only that, partners' awareness of business risks is also increasing, where they are now better equipped to identify, analyze, and mitigate risks that may arise in daily operations. This program is expected to be a model of service that can be applied to other MSMEs in similar sectors..